Hasil Belajar Biologi Siswa yang Diberi Kuis dan Tugas Rumah Pada Penerapan Model Pembelajaran Langsung - Jamilah Jeje (EDU-BIO: Jurnal Pendidikan Biologi, 2018)
This research is a experiment research that aims to know the comparison of learning outcomes between students who were given a quiz with the home tasks on the application of the direct instruction model at class VII MTs Tarbiyah Islamiyah. The research design is post test only control design. The population in this study is all students of class VII MTs Tarbiyah Islamiyah as many as 4 classes. Sampling is done by cluster random sampling. Before the sample is determined the homogeneity test is done. After being declared homogeneous, followed by random technique and obtained class VII-A as experimental-1 class and class VII-B as experiment-2 class. The average post test result of experimental-1 class is 77.2 and the standard deviation is 10.83. The average post test result of experiment-2 class is 67.8 and the standard deviation is 13.2. Technique of data analysis by using “t”test. From the calculation results obtained t0 = 2.74 greater than ttable (either at a significant level of 5% or 1%), meaning H0 is rejected, so it can be concluded that the average learning outcomes of students given the quiz on the application of the Direct instruction model is better than the average learning outcomes Biology of students who are given home tasks on the application of the direct instruction model.Keywords: Quiz, Home Tasks, Direct instruction, Learning Outcomes.